Răspuns :
Răspuns:
c) 4; d) 5
Explicație pas cu pas:
c)
[tex]{4}^{15} - 3 \cdot {4}^{14} - 3 \cdot {4}^{13} - ... - 3 \times 4 = {4}^{15} - 3 \cdot ({4}^{14} + {4}^{13} + ... + 4) = {4}^{15} - 3 \cdot \frac{4 \cdot ( {4}^{14} - 1)}{4 - 1} = {4}^{15} - 3 \cdot \frac{{4}^{15} - 4}{3} = {4}^{15} - {4}^{15} + 4 = \bf 4[/tex]
sau
[tex]{4}^{15} - 3 \cdot {4}^{14} - 3 \cdot {4}^{13} - ... - 3 \cdot 4 = \\ [/tex]
[tex]= {4}^{14} \cdot (4 - 3) - 3 \cdot {4}^{13} - ... - 3 \cdot 4 \\ [/tex]
[tex]= {4}^{14} - 3 \cdot {4}^{13} - ... - 3 \cdot 4 \\ [/tex]
[tex]= {4}^{13} \cdot (4 - 3) - 3 \cdot {4}^{13} - ... - 3 \cdot 4 \\ [/tex]
[tex]= {4}^{13} - 3 \cdot {4}^{13} - ... - 3 \cdot 4 = ... \\ [/tex]
[tex]= {4}^{2} - 3 \cdot 4 = 4 \cdot (4 - 3) = \bf 4 \\ [/tex]
d)
[tex]{5}^{100} - 4 \cdot {5}^{99} - 4 \cdot {5}^{98} - ... - 4 \cdot 5 = {5}^{100} - 4 \cdot ({5}^{99} + {5}^{98} + ... + 5) = {5}^{100} - 4 \cdot \frac{5 \cdot ( {5}^{99} - 1)}{5 - 1} = {5}^{100} - 4 \cdot \frac{{5}^{100} - 5}{4} = {5}^{100} - {5}^{100} + 5 = \bf 5[/tex]
sau
[tex]{5}^{100} - 4 \cdot {5}^{99} - 4 \cdot {5}^{98} - ... - 4 \cdot 5 = \\ [/tex]
[tex]= {5}^{99} \cdot (5 - 4) - 4 \cdot {5}^{98} - ... - 4 \cdot 5 \\ [/tex]
[tex]= {5}^{99} - 4 \cdot {5}^{98} - ... - 4 \cdot 5 \\ [/tex]
[tex]= {5}^{98} \cdot (5 - 1) - ... - 4 \cdot 5 [/tex]
[tex]= {5}^{98} - ... - 4 \cdot 5 = ... [/tex]
[tex]= {5}^{2} - 4 \cdot 5 = 5 \cdot (5 - 4) = \bf 5 \\ [/tex]